Patient-initiated versus fixed-interval patient-reported outcome-based follow-up in outpatients with epilepsy: a pragmatic randomized controlled trial - Liv Marit Valen Schougaard; Caroline Trillingsgaard Mejdahl; Jakob Christensen; Kirsten Lomborg; Helle Terkildsen Maindal; Annette de Thurah; Niels Henrik Hjollund (SpringerOpen, 2019)
Abstract Background The use of patient-reported outcome (PRO) could potentially contribute to the reorganization of the health care system. AmbuFlex is a PRO system used in remote patient monitoring, in which questionnaires are sent to patients at fixed intervals. The PRO data are used by clinicians to decide whether patients need clinical attention. Better self-management and cost-saving follow-up activities may be achieved by letting patients initiate need of contact. We evaluated the effects of patient-initiated PRO-based outpatient follow-up on health care resource utilization, quality of care, and the patient perspective. Methods We conducted a parallel two-arm pragmatic randomized controlled trial at the Department of Neurology, Aarhus University Hospital, Denmark. Outpatients with epilepsy (≥ 15 years old), attending fixed-interval PRO-based follow-up with web-based questionnaires, were randomly assigned in a ratio of 0.55:0.45 to either 1) patient-initiated PRO-based follow-up (open access telePRO) or 2) fixed-interval PRO-based follow-up (standard telePRO). The primary outcome was the number of outpatient hospital contacts related to epilepsy retrieved from a regional registry. Hospitals admissions and emergency room visits were also assessed. Secondary self-reported outcomes including general health, well-being, health literacy, self-efficacy, number of seizures, side effects, confidence, safety, and satisfaction were retrieved from questionnaires. Data were analyzed by the intention-to-treat and per-protocol approaches. Results Between January 2016 and July 2016, 593 patients were randomized to either open access telePRO (n = 346) or standard telePRO (n = 247). At 18 months, no statistically significant differences were found between the arms regarding number of telephone consultations or outpatient visits. Patients in the open access arm had a slightly lower, statistically significant number of emergency room visits than patients in the standard arm. Self-reported mental well-being in the open access arm was slightly, statistically significantly lower than in the standard arm. Other secondary outcomes did not differ statistically significantly between arms. Conclusion This study did not find, as hypothesized, less use of health care resources or improved patient self-management or satisfaction in the patient-initiated PRO-based initiative compared to fixed-interval PRO-based follow-up. Patient-initiated PRO-based follow-up may be used as an alternative to fixed-interval PRO-based follow-up in patients who prefer this approach, but there is insufficient evidence for recommending a system-wide shift to patient-initiated PRO-based follow-up. Trial registration Registered 4 February 2016 with ClinicalTrials.gov: NCT02673580.